1978
DOI: 10.1128/aac.14.5.765
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Characterization of an Escherichia coli Plasmid Coding for Hydrogen Sulfide Production and Drug Resistance

Abstract: An H2S-producing variant of Escherichia coli (strain 142) isolated from a urinary tract infection was found to be resistant to high levels of tetracycline, ampicillin, streptomycin, and sulfonamide. The H2S trait segregated spontaneously at a frequency of 2.5 x 10-3. No segregation was observed for the drug resistance determinants. Neither ethidium bromide nor acridine orange affected the rate of segregation of the drug resistance determinants or the trait for H2S production. Antibiotic resistance and hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In this sense, several bacterial species could be able to use H 2 S as a cellular protector to increase resistance to ROS triggered by bactericidal antibiotics [11]. Enterobacteriaceae, including Salmonella genus, generates H 2 S in their natural environments mainly from thiosulfate [1,4]; however, the biochemistry and physiological roles of this gas in these species remains poorly described [11]. In this work, we propose a model in which H 2 S production against ROS depends on the sulfur source and the presence of the transcriptional regulator of the cysteine regulon, CysB, and the products of the cysJIH operon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, several bacterial species could be able to use H 2 S as a cellular protector to increase resistance to ROS triggered by bactericidal antibiotics [11]. Enterobacteriaceae, including Salmonella genus, generates H 2 S in their natural environments mainly from thiosulfate [1,4]; however, the biochemistry and physiological roles of this gas in these species remains poorly described [11]. In this work, we propose a model in which H 2 S production against ROS depends on the sulfur source and the presence of the transcriptional regulator of the cysteine regulon, CysB, and the products of the cysJIH operon.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, non-sulfur bacteria with mutations that suppress H 2 S production are highly sensitive to several antimicrobial compounds that exert their bactericidal effect via oxidative stress, including several b-lactam antibiotics [11,12]. The converse is also true since an Escherichia coli (E. coli) strain harboring a plasmid coding for proteins involved in H 2 S production, presented increased resistance to several antibiotics [4]. 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 In E. coli and other non-sulfur bacteria, the main mechanism to produce H 2 S is through b-mercaptopyruvate sulfurtransferase (sseA) using cysteine or thiosulfate as a sulfur source [6].…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria that can produce both NO and H 2 S, the two gases were shown to act synergistically in protecting cells against killing by antibiotics (89). Interestingly, plasmid-borne elements enhancing basal H 2 S production were identified in multidrug-resistant patient isolates of E. coli nearly 40 years ago (90,91).…”
Section: Nitric Oxide and Hydrogen Sulfide Protect Against Antibioticmentioning
confidence: 99%
“…The isolate was susceptible to carbapenems and cephalosporins ( Table 1). The study by Jones et al [3] and Harnett et al [9] demonstrated previously that an H 2 S-producing variant of Escherichia coli isolated from a urinary tract infection (UTI) was also found to be resistant to different clinically relevant antibiotics. A previous study by Bailey et al [1] reported the presence of dfrA12, sul3, tet(A), and cmlA1, including other AR genes in E. coli of healthy adults.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Specific biochemical examinations, including the hydrogen sulfide (H 2 S) test, are important for identification of the Enterobacteriaceae species. The production of H 2 S, however, is not a typical characteristic of E. coli, though the H 2 S-producing variants of E. coli have also been reported previously [2,3]. Bacteria can produce H 2 S through orthologous enzymes, and recent studies have implicated H 2 S as a significant signaling molecule by protecting the bacteria from antibiotic-induced damage [4].…”
Section: Introductionmentioning
confidence: 98%